Descautivar the Latin American pedagogic thought: (Des)colonization and (Des)patriarchalization from the feminist critique - Cheron Zanini Moretti; Graziela Rinaldi da Rosa (Universidade Federal do Norte do Tocantins, 2018)
In this paper, we propose to develop the ideas of "descautivar", decolonizing and depatriarchallizing the pedagogy from Latin American theorists feminist, taking them as "sources", which help us (re)create bases epistemological of "us" before the dominant epistemologies. This is a qualitative bibliographic research that was supported by Francesca Gargallo, Luz Maceira Ochoa, Cláudia Korol, Maria Lugones, Marcela Lagarde, among others. Their approximations and dialogues lead us to the understanding of "sorority" and "feminist ethics" as an essential part of a pact of complex relationships in strengthening common experiences of women, especially as to knowing, power and being. In the transformation movement of Popular Education and Pedagogy, we find ways to "descautivar", decolonize and depatriarcalize these relations, but also as ways to (re)exist and resist in the consubstantiality between race, class and gender.